Wavelet Transform Based Technique for Fault Detection and Classification in a 400 kV Double Circuit Transmission Line - Gautam, Neha; Kapoor, Gaurav; Ali, Shoyab (Asian Journal of Electrical Sciences, 2018)
This work proposes a wavelet transform based fault detection and classification technique for the protection of double circuit transmission line. The three phase current signals of both circuits recorded at Bus-1 of the double circuit transmission line power system are used to evaluate the approximate and high frequency detail coefficients at level-1. The proposed scheme is extensively tested using the test system of a 400 kV, 50 Hz double circuit transmission line simulated in MATLAB. The probability of wavelet transform based proposed technique is tested under a extensive deviation of fault parameters, such as fault location, fault type, fault inception time, fault resistance and ground resistance. The test results exemplifies that all types of faults are appropriately detected/ classified.